The Action of Reproductive Fluids and Contained Steroids, Prostaglandins, and Zn2+ on CatSper Ca2+ Channels in Human Sperm - Jeschke, Janice K.; Biagioni, Cristina; Schierling, Tobias; Wagner, Isabel Viola; Börgel, Frederik; Schepmann, Dirk; Schüring, Andreas; Kulle, Alexandra E.; Holterhus, Paul Martin; von Wolff, Michael; Wünsch, Bernhard; Nordhoff, Verena; et al. (Frontiers in Cell and Developmental Biology, 2021)
The sperm-specific Ca2+ channel CatSper registers chemical cues that assist human sperm to fertilize the egg. Prime examples are progesterone and prostaglandin E1 that activate CatSper without involving classical nuclear and G protein-coupled receptors, respectively. Here, we study the action of seminal and follicular fluid as well of the contained individual prostaglandins and steroids on the intracellular Ca2+ concentration of sperm from donors and CATSPER2-deficient patients that lack functional CatSper channels. We show that any of the reproductive steroids and prostaglandins evokes a rapid Ca2+ increase that invariably rests on Ca2+ influx via CatSper. The hormones compete for the same steroid- and prostaglandin-binding site to activate the channel, respectively. Analysis of the hormones´ structure-activity relationship highlights their unique pharmacology in sperm and the chemical features determining their effective properties. Finally, we show that Zn2+ suppresses the action of steroids and prostaglandins on CatSper, which might prevent premature prostaglandin-activation of CatSper in the ejaculate, aiding sperm to escape from the ejaculate into the female genital tract. Altogether, our findings reinforce that human CatSper serves as a promiscuous chemosensor that enables sperm to probe the varying hormonal microenvironment prevailing at different stages during their journey across the female genital tract.